Implementasi dan Pengaruh APM (Anjungan Pendaftaran Mandiri) terhadap Efisiensi Pelayanan di Rumah Sakit Botania - Mulyana, Mulyana; Situmorang, Masriani; Claudia, Claudia (Transpublika Publisher, 2025)
The purpose of this study is to evaluate the implementation and effect of the Automated Registration Machine on service efficiency at Awal Bros Botania Hospital. This study uses observation and interview methods to collect data on the effectiveness of the Automated Registration Point in speeding up the patient registration process. The results showed that the use of Automated Registration Machine at Awal Bros Botania Hospital Batam has improved service efficiency by reducing patient waiting time. BPJS patients who register online can directly use the machine to re-register without having to queue at the counter. The self-registration platform also simplifies the registration process, improves patient satisfaction, and helps the hospital increase productivity. However, there are technical issues such as running out of ink or paper, as well as difficulties for some patients, especially the elderly, in operating the machine. To address this, hospitals need to provide technical support, training for patients, and more helpers around the machines. Self-registration machines also help administrative and medical staff in improving work efficiency, as there are fewer queues at the registration counters.